The “Depressive” Attributional Style Is Not That Depressive for Buddhists - Liu, Michelle T.; Wang, Fei; Peng, Kaiping (Frontiers in Psychology, 2017)
Numerous studies have shown that depression-prone people are characterized by a chronic style of attributing failures to internal, stable, and global causes, sometimes labeled as the “depressive attributional style.” Much less is known, however, about how social-cultural factors such as religious beliefs might modulate these processes. In the current study, we hypothesized that Buddhism's view of ultimate internal controllability plays a buffering role against the depressive attributional style and reduces its negative impacts. We administrated measures of attributional styles and psychological adjustments to a sample of Chinese Buddhists as well as a control group recruited in China. Data analyses showed that Buddhists were more likely to attribute bad outcomes to internal, stable, and global causes, but their well-being was less affected by it. Thus, these results indicate that the “depressive” attributional style is not that depressive for Buddhists, after all.